APLIKASI INVENTORY SYSTEM IT SUPPORT PADA PT ABC - Indah Dwi Lestantri; Noventy Angela; Dimas Fonda (Politeknik Manufaktur Astra, 2011)
Application of inventory data management IT Support is an application used to monitor hardware and software. The application is started from the desire of users to request hardware and software to the IT Support. Application of inventory data management IT Support have warning system warranty, where its use is to remind the IT support in the processing of warranty. In this application can also produce reports. These reports can meet the needs of the IT Support in overseeing hardware and software. This application was built with the programming language PL / SQL. Oracle 10g as a Development tools, DBMS Oracle Database 10g Development Suite and some other software such as Toad 9.0, Internet Explorer 5.0 - Internet Explorer 7.0.